2021
DOI: 10.1200/jco.2021.39.6_suppl.286
|View full text |Cite
|
Sign up to set email alerts
|

Real-world treatment patterns and sequencing for metastatic renal cell carcinoma (mRCC): Results from the Flatiron database.

Abstract: 286 Background: RCC accounts for ~80%‒90% of all kidney cancers worldwide. The mRCC treatment landscape is rapidly changing with the approval of new therapies; data describing real-world (RW) treatment patterns and sequencing are limited. This study investigates the characteristics, treatment patterns, and sequencing for mRCC patients in the RW (December 2015‒May 2020) and post-dual immuno-oncology therapy (IO-IO) approval in the United States (April 2018‒May 2020). Methods: Adults diagnosed with mRCC between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Consistent with the study by Zakharia et al [17] , we observed a marked increase in the uptake of both pembrolizumab + axitinib and ipilimumab + nivolumab combinations since their respective FDA approval. In our study, consistent with the literature [18] , [19] , [20] , [21] , 2L therapies were guided by 1L therapies: patients received TKI monotherapy after IO-based 1L treatment, and received an IO-based therapy after TKI-based 1L treatment. Cabozantinib was the most common 2L therapy among patients receiving IO-based 1L therapy, and nivolumab was the most common 2L therapy among patients receiving 1L TKI monotherapy.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with the study by Zakharia et al [17] , we observed a marked increase in the uptake of both pembrolizumab + axitinib and ipilimumab + nivolumab combinations since their respective FDA approval. In our study, consistent with the literature [18] , [19] , [20] , [21] , 2L therapies were guided by 1L therapies: patients received TKI monotherapy after IO-based 1L treatment, and received an IO-based therapy after TKI-based 1L treatment. Cabozantinib was the most common 2L therapy among patients receiving IO-based 1L therapy, and nivolumab was the most common 2L therapy among patients receiving 1L TKI monotherapy.…”
Section: Discussionsupporting
confidence: 81%
“…The number of patients who are candidates for continuing treatment in Serbia is 35–40%. According to available data from the literature, the number of patients who continue treatment after the failure of the first-line TKI ranges between 26 and 63% in everyday practice ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oral TKI monotherapy is still considered for patients unable to take or to tolerate checkpoint inhibitors, and for those displaying no response to immunotherapy. 1 Oral TKI treatment sequences in mRCC patients have been little studied 2 and may constitute prognostic hallmarks of disease progression. 3,4…”
Section: Introductionmentioning
confidence: 99%
“…Oral TKI monotherapy is still considered for patients unable to take or to tolerate checkpoint inhibitors, and for those displaying no response to immunotherapy. 1 Oral TKI treatment sequences in mRCC patients have been little studied 2 and may constitute prognostic hallmarks of disease progression. 3,4 The frequency and severity of adverse effects associated with TKI treatment remain high in comparison with intravenous chemotherapies, creating a major challenge in the ambulatory management of mRCC patients, whose healthcare pathways involve both hospital and community healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%